A revision of the Chrysobothris femorata (Olivier, 1790) species group from North America, north of Mexico (Coleoptera: Buprestidae) - Wellso, Stanley G.; Manley, Gary V (Zootaxa, 2007)
The Chrysobothris femorata (Olivier, 1790) species group is currently comprised of five species from North American localities north of Mexico. One previously described and synonymized species, C. quadriimpressa Gory & Laporte, 1837 is resurrected. In addition, neotypes are designated for C. femorata, C. rugosiceps Melsheimer, 1845 and C. viridiceps Melsheimer, 1845 as the type specimen for each of these species is lost. A key is included to facilitate identification of the 12 species, 11 of which have deciduous trees as hosts and one species from woody goldenrod, Chrysoma pauciflosculosa (Michx.). Six new species of Chrysobothris are described herein: C. mescalero, C. seminole, C. wintu, C. comanche, C. caddo, and C. shawnee. The new species are each fully described and the elytra, male genitalia, and female pygidium (8th abdominal tergite) of all species are illustrated.